Estimating occupational exposure to carcinogens in Quebec. Issue 9 (26th June 2013) - Labrèche, France; Duguay, Patrice; Ostiguy, Claude; Boucher, Alexandre; Roberge, Brigitte; Peters, Cheryl E.; Demers, Paul A.
Abstract Background We estimated the extent of exposure to occupational carcinogens in Quebec, Canada, to help raise awareness of occupational cancers. Methods Proportions of workers exposed to 21 recognized and 17 probable carcinogens (according to Quebec occupational health regulation and the International Agency for Research on Cancer [IARC] classification) were extracted from various sources: workplace monitoring data, research projects, a population survey, radiation protection data, exposure estimates from the Carcinogen Exposure Canada (CAREX Canada) Project database, and published exposure data. These proportions were applied to Quebec labor force data. Results Among the 38 studied, carcinogens with the largest proportions of exposed workers were solar radiation (6.6% of workers), night shift work/rotating shift work including nights (6.0%), diesel exhaust fumes (4.4%), wood dust (2.9%) and polycyclic aromatic hydrocarbons (2.0%). More than 15 carcinogens were identified in several industrial sectors, and up to 100, 000 young workers are employed in these sectors. Conclusion Although crude, estimates obtained with different data sources allow identification of research and intervention priorities for cancer in Quebec. Am. J. Ind. Med. 56:1040–1050, 2013. © 2012 Wiley Periodicals, Inc.